PENGUASAAN MATERI DAN KEMAMPUAN MENULIS PENYELESAIAN SOAL MATEMATIS GURU MATEMATIKA - Heryanto Tan; Sugiatno Sugiatno; Agung Hartoyo (UNIVERSITAS TANJUNGPURA, 2020)
This research aims to get a description about the mastery of the mathematics materials and the ability in writing the mathematical solution among mathematics teachers of senior high school in Pontianak and the relationship between them. This research is a descriptive research through document and result analysis of Uji Kompetensi Profesional Guru (UKPG) Senior High School in 2016. Materials mastery of mathematics teacher is measured by the final score and understanding of UKPGs selected questions, while the ability in writing mathematical solutions is measured by score of the writing and understanding the writing component in answering all of UKPGs essay questions. Result of this research shows that most teachers got the final score below 55.0. Most mathematics teachers got the score below 47.5 in writing up solution. The higher the mastery of materials, the higher the ability in writing the mathematical solutionKeywords : Mastery of mathematics materials, Ability in writing the mathematical solution